An Essential Elements in Virtual Land Buying Transactions as Digital Asets in Metaverse Based onn Indonesian Positive Law - Billa Ratuwibawa Nyimasmukti; Mustika Setianingrum Wijayanti; Dewi Bella Juniarti (Universitas Negeri Semarang in collaboration with Ikatan Penulis Mahasiswa Hukum Indonesia, 2023)
Virtual land as a blockchain-based digital asset in the metaverse is becoming popular and is considered to have high investment potential. There are no ordinance governing the ownership and the trading transaction (buying and selling) of virtual land in Indonesia, giving rise to debates regarding the fulfillment of the essential elements of trading virtual land which consists of objects and prices. Consider, the determination of a thing included in the object is based on the provisions in the law of objects conforming to the Civil Code which is closed. In addition, the price used in trading is stated in cryptocurrency, even though based on Article 35 of Central Bank of Indonesia Regulation Number 18/40/PBI/2016 and Article 8 paragraph 2 of Central Bank of Indonesia Regulation Number 19/12/PBI/2017 have explained the prohibition on payment with cryptocurrency or virtual currency. Whether or not the essential elements in a transaction can result in the transaction being declared null and void. The normative-juridical method uses secondary data, including: primary, secondary and tertiary legal materials. In addition, this research utilizes the legal and conceptual approach used by this research. The results indicated that the object element in the virtual land trading transaction in the metaverse has been fulfilled, but the price element is not fulfilled thus the framework of the agreement that should be embedded in the virtual land transfer transaction using cryptocurrency is swap assets, not trading.